Implementasi Rapid Application Development dalam membangun sistem pengelolaan keuangan Homestay Linia berbasis web - Julians, Adhe Ronny; Iriani, Ade; Sembiring, Irwan (AITI, 2024)
In running a business, the ease of managing financial data is essential because it is closely related to how income and expenditure data can be managed properly. The absence of an efficient system for managing financial data is a problem encountered in the object of this research, namely Homestay Linia, wherein managing the financial data in question, there are still certain complications, which result in financial data being inaccurate and irregular, related to these problems, it is necessary to build a financial management system. In developing the system, researchers use the Rapid Application Development method and will conduct system testing using the Black Box Testing method and User Satisfaction Survey through Online Questionnaires. The results showed that the system that has been built gets 100% positive reviews given by respondents. It shows that the system can help business activities effectively and efficiently.